The Effectiveness Of A Virtual Reality Technology In Training Students By Assessing The Motivation, Motor Performance Scores, And Acceptance - Hamizi, Muhammad Aminuddin Akmal Bin Mohd (2023)
This study aims to identify the effectiveness of VR technology in training students, specifically in physical exercise categorized as individual recreational sports, by measuring the motor performance scores and motivation and determining the acceptance of technology.